HUBUNGAN HORMON ADAPTASI FISIOLOGI DAN PSIKOLOGI PADA MASA NIFAS - AZ-ZAHRA, HASNA ZAQIYAH; -, Tonasih; Yulianti, Ria; Musfiroh, Sri; Amalia, Ainaya Rizki Nur; Angelita, Adinda; Amalia, Rahma; Nadila, Anggi; Putri, Nabilla Muflih Setiana (Universitas Prima Indonesia, 2023)
Postpartum depression is a psychological disorder of the postpartum period that is more dangerous than postpartum depression. Postpartum depression can have serious consequences for the baby's development as well as the mother's social life. To predict the incidence of postpartum depression, early detection is essential. The aim of this study was to describe the results of the seventh day postpartum depression screening in the city of PMB S Malang. Method:The design of this study was descriptive with a population of 72 postpartum mothers, the sample size was 57 who were simply randomized. Seeking aid: EPDS Questionnaire. Result: The results showed that up to 22.8% of postpartum mothers suffered from postpartum depression. Postpartum mothers with EPDS score of 10 are mothers aged >35 years old, working mothers, high school graduates, nuclear families, and some children from 2 to 3 people. Conclusion: Even in small amounts, postpartum depression can negatively impact a mother's mental health and future child development, which is why early detection efforts need to be stepped up